Review of Utilization of Coal, Natural Gas and Hydro for Sustainable Power Generation in Nigeria - Akeem Adekunle Adebesin; Taiwo S. Amosun (Borobudur Engineering Review, 2022)
The geometric increase in a nation’s population vis- a- vis the increase in energy demand in order to power the various sectors of the economy is a source of concern to all citizens and sundry. This paper presents an overview on the alternative sources of power generation and its associated problems and prospects in Nigeria. It starts with historical review of development and demonstrates the reasons. It also goes further to explain the need for using coal, natural gas and hydro means for power generation. Following this, different sources of power generation approaches are compared in order to determine what source is best to consider and the possible energy harvesting means are reviewed. Furthermore, state of the art technology known as carbon capture system is developed and x- rayed. Finally, conclusions are drawn based on the reviewed documents cited in this paper and a research work is initiated.